Recovery components as determinants of the health-related quality of life among patients with schizophrenia: structural equation modelling analysis. - Ho WWN; Chiu MYL; Lo WTL; Yiu MGC (Australian & New Zealand Journal of Psychiatry, 2010)
Objective: The Substance Abuse and Mental Health Services Administration (SAMHSA) National Consensus Statement on Mental Health Recovery proposed 10 recovery components as guiding principles for fostering recovery among people with severe mental illness. Although researchers have recognized a close association between patient-oriented recovery and health-related quality of life (HRQOL), the relation between the recovery components and patients' self-reported HRQOL is still unknown. The purpose of the present study was therefore to use structural equation modelling to predict HRQOL of schizophrenia outpatients from the recovery components proposed by SAMHSA. Methods: The recovery status of 201 outpatients with schizophrenia, schizophreniform, or schizoaffective disorder was measured using 12 variables that indicate the outcome of 10 recovery components. Canonical correlation analysis was applied to screen variables that are highly correlated with HRQOL. Valid variables were then used to build a structural model that predicted individuals' HRQOL as indicated by the World Health Organization Quality of Life Measure Abbreviated (WHOQOL-BREF (HK)). Results: The bestfit model was able to explain 80.7% of the variance in WHOQOL-BREF outcome. The model demonstrated significant direct and indirect effects of five recovery components on HRQOL. The effect of psychosocial symptoms on HRQOL was highest (total ß = -0.64), followed by sense of personal agency (total ß = 0.58), sense of optimism (total ß = 0.54), perceived support (total ß = 0.47), and internal stigma (total ß = -0.42). Conclusion: The recovery components proposed by the SAMHSA consensus statement provided a useful framework to explain HRQOL of outpatients with schizophrenia. The present model indicated a moderate to large effect of five major recovery components on HRQOL. It showed that patients' perceptions of support, optimism, and personal agency were influenced by psychosocial symptoms and internal stigma. This empirical study supported the use of recovery principles, such as resilience building or mastery-based intervention to improve the QOL of community dwellers with schizophrenia.